Professional Scepticism, Independence, Information Technology, Auditor Competence, And Audit Quality - M. Rasuli; Arumega Zarefar; Atika Zarefar; Razana Juhaira Johari (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to obtain empirical evidence regarding the effect of professional scepticism, independence, information technology, and auditor competence on audit quality. Methodology/approach: This study uses a quantitative approach with primary data in the form of questionnaires. Respondents of this study were 68 auditors of BPK RI Representative of Riau Province. Regression analysis using the PLS-SEM method. Findings: The results showed that professional scepticism and BPK auditor competence significantly positively affected BPK audit quality. Other results show that independence and information technology do not significantly affect BPK audit quality. Practical implications: These results provide a new understanding of independence and information technology in conducting audits in the public sector. Although BPK is an external auditor for all government agencies, the income of BPK employees or auditors comes from the government, so independence is not quite appropriate to be pinned on BPK auditors. Still, the objective attitude of each BPK auditor in carrying out audits at government agencies must be improved. Originality/value: These results contribute to the development of literature on the determinants of audit quality.